An endogenous visual process with nomadism of means and images (Revista Apotheke, 2022)
This visual essay is a clipping of a broader research that involves the migration of images produced at different times, which migrate as nomads from one medium to another in order to integrate with the time and space in which I live today, a reflection of my migration to Marabá, a city located in the Amazon paraense and place at the same time diverse and antagonistic to that of my origin. The choices are somehow the result of this antagonism, the distance traveled by the migration of region brought me closer to myself, perhaps the effect of the Amazon distances that so vast, seem at each step so far more further, contributing to an endogenous visual process, in which images of the past are invariably engendered by exogenous perception that never moves away,  as a need for visual art to incorporate, exchange and simulate in their means the human experience of life, themselves, dumb and inert bodies but fully capable of induce the thought to those who in the fruition animate them. Two experiments will be shown, in one, the image of a recent painting and photograph migrate to a 23-year-old ago etching plate, and the other an old drawing and a recent photograph migrate to a woodcut with historical carving and printing processes and from them to a  hybridized print with digital process.
Keywords: endogenous image; exogenous image; etching